HERBIVOROUS ANIMALS AN ULARNING ANALOG AND PSYCHOTROPIC SUBSTANCES CONTRADICT EACH - Gazibekov Khurshid Iskandarovich (International Journal of Business, Law and Political Science, 2024)
The interplay between legal regulations concerning herbivorous animals, their analogs, and psychotropic substances represents a complex and multifaceted issue within legal and ethical frameworks. The legal classification and control of psychotropic substances often clash with the regulation of herbivorous animals and their by-products, leading to significant legal ambiguities and challenges. Herbivorous animals and their by-products are generally subject to regulations that ensure animal welfare, food safety, and environmental protection. In contrast, psychotropic substances are regulated to prevent misuse and protect public health. The overlap and divergence between these regulatory domains highlight a legal conundrum, especially when considering the use of animal-derived products in contexts that intersect with psychotropic substances. Despite existing regulations, there is a notable lack of comprehensive analysis on how legal frameworks governing herbivorous animals and psychotropic substances interact. This gap in legal scholarship hinders the development of coherent policies that address both animal welfare and public health concerns.This study aims to explore the legal contradictions and conflicts between the regulations of herbivorous animals and psychotropic substances. It seeks to identify and analyze the points of contention and the impact these conflicts have on legal practices and policy-making. The analysis reveals significant legal contradictions where the use of animal-derived substances in psychotropic contexts often challenges existing regulations. This misalignment underscores the need for legal reforms that harmonize the treatment of herbivorous animals and the regulation of psychotropic substances.This study introduces a novel perspective by linking animal welfare and psychotropic substance regulation, highlighting the previously underexplored intersections between these domains.The findings suggest a need for interdisciplinary legal reforms and policy adjustments to address the conflicts between these regulatory areas. By bridging the gap between animal welfare laws and psychotropic substance regulations, the study advocates for more integrated and coherent legal frameworks to enhance both public health and animal welfare